Adipose tissue-specific Nrf2 knockdown inhibits the cGAS-STING pathway to attenuate inflammation in obese mice - Zhao, Lin; Tuerxunaili, Lina; Shi, Guiyun; Wu, Mengyue; Jiao, Yi (Frontiers in Endocrinology, 2026)
BackgroundObesity is a chronic, non-infectious inflammatory disease associated with oxidative stress and is triggered by adipose tissue expansion. Nuclear factor erythroid 2-related factor 2 (NRF2) is a core antioxidant defense system transcription factor in adipose tissue and is associated with the cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) pathway. However, the regulatory roles of NRF2 and the cGAS-STING pathway in obesity-related metabolic disorders remain unclear. Therefore, this study aimed to evaluate the effects of adipose tissue-specific Nrf2 knockout (Nrf2△/adipo) on obesity-related metabolic phenotypes and inflammation in mice.MethodsAn Nrf2△/adipo mouse model was constructed, followed by high-fat diet (HFD) intervention to induce obesity. Additionally, various tests, including glucose tolerance test, RNA sequencing, and western blotting, were performed to elucidate the mechanism of Nrf2 in obesity in the mice.ResultsNrf2Δ/adipo mice exhibited reduced body weight, body fat, triglyceride levels, and total cholesterol content and improved glucose and insulin tolerance compared with HFD Nrf2flox/flox controls. Nrf2Δ/adipo mice showed decreased body weight and significant increases in oxygen and carbon dioxide consumption and energy expenditure. Transcriptome sequencing and pathway enrichment analysis revealed that adipose tissue-specific Nrf2 knockdown significantly downregulated cGAS-STING pathway-related genes and their corresponding proteins. Further mechanistic analysis revealed increased mitochondrial DNA copy number in adipose tissue after Nrf2 knockdown, along with decreased cGAMP and malondialdehyde levels. Flow cytometry analysis revealed a reduction in M1 macrophages following adipose tissue-specific knockout of Nrf2. Enzyme-linked immunosorbent assay revealed decreased expression of proinflammatory factors.ConclusionSpecific Nrf2 knockdown in adipose tissue attenuates obesity-induced adipose tissue inflammation by inhibiting the cGAS-STING pathway, providing a novel therapeutic strategy targeting the adipose-specific antioxidant-inflammatory regulatory network.